Autoantibodies against ZnT8 are rare in Central-European LADA patients and absent in MODY patients, including those positive for other autoantibodies - Heneberg, Petr; Šimčíková, Daniela; Čecháková, Marie; Rypáčková, Blanka; Kučera, Petr; Anděl, Michal (Journal of diabetes and its complications, 2019)
BACKGROUND: Testing for autoantibodies against the zinc transporter ZnT8 (ZnTA) is becoming routine in pediatric diabetes. However, available data are inconclusive when focusing on adult-onset diabetes, including autoimmune diabetes, which does not require insulin at diagnosis (LADA). BASIC PROCEDURES: We examined the ZnTA prevalence and titers and matched them with the clinical phenotype and PTPN22 genotypes of Czech LADA patients who were positive for GADA and/or IA2A and had a fasting C-peptide level >200 pmol/L at diagnosis as well as HNF4A-, GCK- or HNF1A-MODY patients and healthy controls. MAIN FINDINGS: Most LADA patients were negative for ZnTA, and the sensitivity of the assay was only 18-20% for patients with LADA-like progression to insulinotherapy compared to healthy controls. In LADA patients, there was no association between the ZnTA and PTPN22 risk genotypes. LADA patients positive for ZnTA had a lower BMI than those positive for other autoantibodies alone. Importantly, MODY patients were completely negative for ZnTA, and the levels of ZnTA in MODY patients were similar to those in healthy controls. CONCLUSIONS: ZnTA quantification did not improve LADA diagnosis. However, positivity for ZnTA can be used as a negative MODY pre-diagnostic criterion even in the region of Central and East Europe, where other islet cell autoantibodies are common in MODY patients.
Keywords: Adult-onset autoimmune diabetes; PTPRN; biologické markery; zinkový transportér 8; Disease Progression; lidé; Middle Aged; tyrosinfosfatasa nereceptorového typu 22; LYP; fenotyp; Female; inzulin; progrese nemoci; diabetes mellitus 1. typu; Phenotype; Humans; Genotype; LADA; Česká republika; Diabetes Mellitus, Type 1; Zinc Transporter 8; Zinc transporter ZnT8; autoprotilátky; lidé středního věku; Biomarkers; diabetes mellitus 2. typu; mužské pohlaví; Diabetes Mellitus, Type 2; BMI; Czech Republic; ženské pohlaví; Protein Tyrosine Phosphatase, Non-Receptor Type 22; genotyp; Male; hypoglykemika; Hypoglycemic Agents; Autoantibodies; Insulin